Association of Fibrinogen with Parkinson Disease in Elderly Japanese-American Men: A Prospective Study - Wong, K.T. (S. Karger AG, 2010)
BACKGROUND: The purpose of this prospective study was to examine whether fibrinogen level is associated with Parkinson disease (PD) for both prevalent and incident cases. METHODS: The Honolulu Asia-Aging Study is a longitudinal study of Japanese-American men based on the Honolulu Heart Study birth cohort. The original cohort consisted of 8,006 participants with selective service records who were living on the island of Oahu, Hawaii, in 1965. For this analysis, baseline was defined as the 1991–1993 examination (n = 3,845) when men were aged 71–93 years old. Multivariate logistic regression and Cox proportional hazards models were used, adjusting for potential confounders. RESULTS: We identified 61 prevalent cases and 61 incident cases of PD during the follow-up. High fibrinogen level (presence in the top quintile) was associated with higher frequency of PD for both prevalent (OR = 2.07, 95% CI = 1.10–3.88, p = 0.024) and incident cases (HR = 3.05, 95% CI = 1.34–6.97, p = 0.008) among men aged 76–93 years, after adjusting for age, smoking, and low-density lipoprotein cholesterol. CONCLUSIONS: These results suggest high fibrinogen level is associated with increased risk of PD among men over 75 years.